1970
DOI: 10.1044/jshr.1302.395
|View full text |Cite
|
Sign up to set email alerts
|

Use of Contrastive Stress by Preschool Children

Abstract: Twenty preschool children were asked to describe pairs of pictures, the second of which contrasted with the first in terms of agent, action, or object. The children showed a clear tendency to stress the part of the description corresponding to the contrasting element. This demonstrates mastery of contrastive stress patterns (in absence of any formal teaching) by young children. The technique provides a controlled means of eliciting this aspect of speech in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
3

Year Published

1978
1978
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 0 publications
1
65
0
3
Order By: Relevance
“…There is no currently available data about children's use of accenting during reference comprehension. The only evidence of children's sensitivity to the relationship between accenting and discourse status comes from production studies, which show that English-speaking preschoolers produce adult-like accenting in their own speech, preferring accented tokens for new referents, and unaccented ones for given referents (Wieman, 1976;Hornby & Hass, 1970;MacWhinney & Bates, 1978). However, these findings do not mean that children can also use accenting during comprehension.…”
Section: Does Accenting Guide Preschoolers' Reference Interpretation?mentioning
confidence: 83%
“…There is no currently available data about children's use of accenting during reference comprehension. The only evidence of children's sensitivity to the relationship between accenting and discourse status comes from production studies, which show that English-speaking preschoolers produce adult-like accenting in their own speech, preferring accented tokens for new referents, and unaccented ones for given referents (Wieman, 1976;Hornby & Hass, 1970;MacWhinney & Bates, 1978). However, these findings do not mean that children can also use accenting during comprehension.…”
Section: Does Accenting Guide Preschoolers' Reference Interpretation?mentioning
confidence: 83%
“…For example, Hornby and Hass (1970) observed a more frequent use of emphatic accentuation to mark subject contrast than verb-and object-contrast. Furthermore, children may or may not use accentuation to the same extent as adults do.…”
Section: Productionmentioning
confidence: 99%
“…More specifically, earlier case studies reported that some Englishspeaking children began to use emphatic accentuation to introduce contrastive information at about age 2 (Weir, 1962;Brown, 1973). Later experimental studies showed that English-and German-speaking children could use emphatic accentuation to mark contrastive narrow focus in different positions in SV, SVO and SVindirectOdirectO sentences at the age of 3-5 years and that there was an increase in the use of empathic accentuation in older children (for corrective contrastive focus see Hornby and Hass, 1970;MacWhinney and Bates, 1978;Baltaxe, 1984;Wells et al, 2004; for non-corrective contrastive focus see Mü ller et al, 2006). In these studies, children were asked to correct the experimenter's description of pictures (e.g.…”
Section: Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies of production have demonstrated that children aged 3 ; 0 to 5; 11 can use accent placement to achieve narrow focus, in order to do corrections (Hornby & Hass, 1970 ;Hornby, 1971 ;Macwhinney & Bates, 1978), suggesting that this ability is well developed in the preschool period. On the other hand, Cruttenden (1985) found that his ten-year-old subjects, while performing above chance level, were significantly worse than adults at assigning to the correct picture sentences which differed in focus/accent structure : John's got *four oranges vs. John's got four *oranges.…”
Section: Communicative Areas Of Intonation : Structure and Developmentmentioning
confidence: 99%